A New Wave of Social Democracy? Policy Change across the Social Democratic Party Family, 1970s–2010s. Issue 1 (20th January 2022) - Manwaring, Rob; Holloway, Josh
Abstract: Social democracy is in a state of change and flux, and the electoral fortunes of many centre-left political parties are poor. This article offers an analysis of the current trajectory of the centre left, by detailing a systematic mapping of policy change across the family of social democratic political parties. Many of the parties, especially in the 1990s, took a 'third way' turn, or a shift to what has been called the 'new social democracy'. Yet, the 'third way' label is a poor descriptor to capture the changing policy profile and dynamics of the family of mainstream centre-left political parties. In Adam Przeworski's view, there have been four main waves of social democracy. We employ the 'wave' frame to examine if there is an emergent, fifth, breaking wave of social democracy. Overall, we find that social democratic parties have moved beyond the 'third way'; they are shifting leftwards, but they are a new kind of 'left' from that of previous decades.